Typology of tasks for the use of vocabulary in different types of speech activity (Eurasian Journal of Learning and Academic Teaching, 2024)
This article focuses on the analysis of enhancing lexical skills in the process of teaching skills of communication and methods of organizing the stage of speech activity and different types of them